Eksistensi Nilai-Nilai Dakwah di Kalangan Generasi Z Melalui Media Sosial Kecamatan Glenmore Kabupaten Banyuwangi - Mahrus Hadi; Khoiruman, Muhamad Alfi (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to investigate the existence of da'wah values ​​among Generation Z through the use of social media in Glenmore District, Banyuwangi Regency. Generation Z, which is a group that predominantly uses digital technology, often interacts with Islamic preaching values ​​through platforms such as Facebook, Instagram and TikTok. This research is based on the importance of understanding how social media facilitates the spread of da'wah values ​​in contexts that are relevant to the younger generation. The research method used is a qualitative approach with data collection techniques through in-depth interviews and content analysis of preaching posts spread on social media. The research results show that Generation Z in Glenmore District shows a high level of participation in receiving and spreading da'wah messages through social media. They use this platform not only for social interaction but also as a means to strengthen their religious identity. This research provides in-depth insight into how social media can be an effective tool in maintaining and developing religious practices among the younger generation, especially in local contexts such as Glenmore District, Banyuwangi Regency.